THE RELATIONSHIP OF COGNITIVE FUNCTION AND INDEPENDENCE ACTIVITIES OF DAILY LIVING (ADL) IN ELDERLY AT PANTI DARUSSA'ADAH AND AN-NUR LHOKSEUMAWE - Cut Sidrah Nadira; Mulyati Sri Rahayu (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Aging causes a lot of changes in elderly’s physiologic function. It could be physical, mental or functional changes, including cognitive function. Cognitive function needed for performing ADL tend to decrease in elderly. Decreasing in cognitive function will cause disturbance in fulfil daily requirements so that increasing the dependency on others to help performing ADL. This study purpose to analyze relationship between cognitive function and independent level in performing ADL in elderly at panti Darussa’adah and An-Nur lhokseumawe using analytical cross-sectional design with purposive sampling technique. The data was analyzed by chi-square for the statistical test. Population for this study was elderly who lives in panti Darussa’adah and An-Nur by September 2017. Data obtained from 30 participants based on inclusion and exclusion criteria. Variables of this study are cognitive function and independent level in performing ADL. The result showed that half participants (50%) had a severe cognitive impairment. Most of them (53,3%) need helps to perform ADL. There is no significant relationship between cognitive function and independent level in performing ADL in elderly at Panti Darussa’adah and An-Nur lhokseumawe (p = 0,209). However, it is suggested that elderly should have a mental activity for maintaining their cognitive function.